TINJAUAN YURIDIS PEMBERIAN GRASI TERHADAP PELAKU TINDAK PIDANA KORUPSI DIKAITKAN DENGAN TEORI PEMIDANAAN - Karefna, Ditya; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Clemency is a pardon in the form of amendment, mitigation, reduction, or elimination of the implementation of a criminal offense given by the president. Granting clemency to prisoners is regulated in the Indonesian constitution, namely Article 14 Paragraph (1) of the Constitution of the Republic of Indonesia that,